2018
DOI: 10.1002/2017ja025106
|View full text |Cite
|
Sign up to set email alerts
|

Intervals of Intense Energetic Electron Beams Over Jupiter's Poles

Abstract: Juno's Jupiter Energetic particle Detector Instrument often detects energetic electron beams over Jupiter's polar regions. In this paper, we document a subset of intense magnetic field‐aligned beams of energetic electrons moving away from Jupiter at high magnetic latitudes both north and south of the planet. The number fluxes of these beams are often dominated by electrons with energies above about 1 MeV. These very narrow beams can create broad angular responses in the Jupiter Energetic particle Detector Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

8
1

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…Prior to the arrival of NASA's Juno spacecraft at Jupiter, the wave-particle interaction processes responsible for auroral acceleration at the giant planets were nevertheless assumed to be similar to what is observed in the terrestrial magnetosphere. Contrary to the initial lack of such observations, later spacecraft passes indicated the presence of strong parallel electric fields, coherent particle acceleration, and inverted-V structures Mauk et al, 2018;Paranicas et al, 2018). Juno also observed ion conics on auroral field lines , which may be the result of field-aligned electron beams and the associated broadband whistler waves (Tetrick et al, 2017) similar to the those observed at Earth although at much higher energies.…”
Section: 1029/2019ja027403mentioning
confidence: 82%
“…Prior to the arrival of NASA's Juno spacecraft at Jupiter, the wave-particle interaction processes responsible for auroral acceleration at the giant planets were nevertheless assumed to be similar to what is observed in the terrestrial magnetosphere. Contrary to the initial lack of such observations, later spacecraft passes indicated the presence of strong parallel electric fields, coherent particle acceleration, and inverted-V structures Mauk et al, 2018;Paranicas et al, 2018). Juno also observed ion conics on auroral field lines , which may be the result of field-aligned electron beams and the associated broadband whistler waves (Tetrick et al, 2017) similar to the those observed at Earth although at much higher energies.…”
Section: 1029/2019ja027403mentioning
confidence: 82%
“…The downward flux remained less than the FUV with the exception of two spikes at 13:27 and 13:32. A high energy component ("penetrating radiation") is observed as described by Paranicas et al (2018) and Mauk et al (2018). We note that the magnetic mapping in this region may be less accurate than in other sectors.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 85%
“…We believe the counts in this plot are due to electrons that come in through the JEDI collimator and then fully penetrate the SSD; this can occur for any electrons with energies >420 keV Paranicas et al, 2018). These electrons deposit only a fraction of their energy in the SSD.…”
Section: Io Flyby Datamentioning
confidence: 96%
“…We compare the data with findings of previous modeling that attempted to reproduce radial flux profiles of energetic charged particles measured by other spacecraft. We believe the counts in this plot are due to electrons that come in through the JEDI collimator and then fully penetrate the SSD; this can occur for any electrons with energies >420 keV Paranicas et al, 2018). Since JEDI was not designed to study Jupiter's radiation belts, we first discuss some features of the signal in the radiation belts.…”
Section: 1029/2019gl085393mentioning
confidence: 99%